Next-Generation Sequencing Technology Combined With Multiplex Polymerase Chain Reaction as a Powerful Detection and Semiquantitative Method for Herpes Simplex Virus Type 1 in Adult Encephalitis: A Case Report - Chen, Weibi; Wu, Yingfeng; Zhang, Yan (Frontiers in Medicine, 2022)
Background: Traditional testing for specific microbes or categories of central nervous system (CNS) infectious diseases is often limited in sensitivity and timeliness. However, failure to initiate a timely etiological diagnosis and corresponding treatment in patients with neurologic infections contribute to poor outcomes. Case summary: A 58 year-old male presented acutely with fever, abnormal mental behavior, seizures and decreased consciousness. Brain magnetic resonance imaging (MRI) showed an abnormal FLAIR/T2 signal mainly in the left thalamus, temporal lobe, insular lobe and bilateral hippocampus. To identify the pathogen, the cerebrospinal fluid (CSF) sample of the patient was used for metagenomic next-generation sequencing (mNGS) analysis and multiplex polymerase chain reaction (mPCR). The results showed 188 herpes simplex virus (HSV-1)-specific sequences. After acyclovir and foscarnet sodium treatment, the ratio of HSV-1/internal reference reads decreased from 813/493 to 695/1961, which coincided with clinical remission. Conclusions: This study indicates that mNGS combined with mPCR may be an effective method for etiological diagnostic and dynamic clinical surveillance for HSV-1 encephalitis.